INFLUENCE OF COMBINED CARRIAGE OF LIPID TRANSPORTING SYSTEM GENES POLYMORPHISMS ON THE GRADE OF CORONARY ATHEROSCLEROSIS IN UNSTABLE ANGINA PATIENTS - A. S. Eshpulatov; Sh. U. Hoshimov; A. B. Shek; R. D. Kurbanov (Российский кардиологический журнал, 2016)
Aim. To study the specifics of lipid metabolism and involvement of coronary flow according to combination carriage of “ε4”-allele ε2ε3ε4 polymorphism of gene apolipoproteine Е (Apo Е) and “S2”-allele SstI polymorphism of gene apolipoproteine СIII (Apo СIII) in unstable angina patients.Material and methods. Totally, 141 patients assessed, with unstable angina and angiographically proven coronary atherosclerosis. Comparison group — 50 healthy persons. Genotyping of ε2/ε3/ε4 polymorphism gene Apo Е and SstI polymorphism gene Apo СIII was done by PCR.Results. 37 were selected to one group of patients with the carriage of “harm” alleles: “ε4” and “S2” — (I group), versus the others (II group) — 104 patients. In comparison of lipid profiles, I group showed significantly higher levels of total cholesterol (238,0±54,3 mg/dL) and low density cholesterol (LDL) (154,7±51,5 mg/dL) (Р<0,05), than levels of TC (220,6±39,8) and LDL (138,8±37,6) in II group. Also, in I group patients there was lower HDL cholesterol (34,1±6,3, P<0,05), comparing to II group (36,8±6,8). Level of apolipoproteide В (Apo В) was slightly higher (115,0±24,9 mg/dL), and level of apolipoproteide А-I (Apo А-I) — lower (133,8±21,3) in group I, that led to significantly higher relation of Apo-B/Apo-AI — 0,9±0,3 (P<0,05), comparing to group II (107,0±25,7, 139,1±22,2 and 0,8±0,2), respectively.Conclusion. Carriage of alleles “S2” SstI polymorphism gene apo CIII and “ε4” ε2ε3ε4 polymorphism gene Apo Е is predetermining factor for development of coronary atherosclerosis and atherogenic dyslipidemia among uzbeks. According to coronary arteriography, in the I group patients had more commonly three — and multivessel disease (Р<0,05).